VISUAL POLLUTION IN NATURAL AND LANDSCAPE PROTECTED AREAS: CASE STUDIES FROM POLAND AND SLOVAKIA - Szczepańska, Magdalena; Wilkaniec, Agnieszka; Škamlová, Lucia (Quaestiones Geographicae, 2019)
The phenomenon of outdoor advertising is particularly worrying in protected areas due to the limitation and depreciation of natural and landscape assets. The paper aims to identify and compare legal provisions concerning the advertising policy in relation to naturally and visually precious areas in Poland and Slovakia. Moreover, it determines the scale of visual pollution in a protected area – trends in the location, size, form and influence on the surroundings and perception. In both analysed countries there are regulations that would not bring the desired effects regarding the advertising policy. Advertisement devices are present in settlements and at significant road points, entrances to facilities connected with tourism. A point of concern is that they are frequently placed in the most precious landscape areas.